Effectiveness of the WaveOne Gold system in preparing long oval canals with unique instruments and in sequential mode - Kublitski, Prescila Mota de Oliveira (2021)
The aim of this study was to evaluate variation in volume, percentage of non-instrumented areas and debris after preparing long oval canals with the WaveOne® Gold (WOG) system with two techniques: using each instrument of the system (single-file - SF) or use of all files in the system sequentially (multiple-file - MF). Fifty lower human incisors were selected, distributed in five groups (n = 10). After verification of the root dimension with manual files, all specimens were submitted to microcomputed tomography (μCT) for analysis of volume variation, percentage of non-instrumented areas and debris after preparation. The specimens were prepared with WOG instruments, using SF and MF mode. The data were analyzed for normality and homogeneity of variance. Depending on the outcome, One-Way ANOVA tests followed by Games-Howell or Tukey, and Kruskal-Wallis followed by Dunn were applied. All groups showed a variation in total volume and regardless of the technique used, the cervical third had greater magnification when compared to the apical one (p <0.05). Regarding the percentage of non-instrumented areas and debris, significant differences were observed for WOG Medium versus WOG Small to WOG Medium (p <0.05). Both techniques, SF and MF, provided volume variation after preparation, with persistence of non-instrumented areas and debris. However, better results occur when there has been greater enlargement of the root canal.